Pembelajaran Darurat Selama Masa Pandemi Covid-19: Daring/E-learning Sebagai Solusi Kegiatan Pembelajaran dengan Berbagai Kelebihan & Kekurangannya - Kuntum Annisa Imania; Siti Husnul Bariah; Dian Rahadian; Yuniar Purwanti (Institut Pendidikan Indonesia, 2021)
Abstract - This study aims to describe the conditions of online learning during the emergency response period (covid-19), online learning activities certainly have advantages and disadvantages, especially during the Covid-19 emergency, where every educational institution and even the government does not have special preparations in the implementation of online learning, because The author mentions this condition is